A Christian Concubine in Commodus’ Court? - Anise K. Strong (Eugesta, 2014)
In the late 2nd century CE, Marcia, a “god-loving woman” and the principal concubine of the Roman Emperor Commodus, interceded with her lover to free a number of Christian prisoners who had been sentenced to slave labor in the mines of Sardinia (Hippolytus, Philosophumena, 9.2.12.). Such an act of charity and clemency might have been expected to earn her a place among the Catholic saints. On the other hand, Marcia’s patronage of a persecuted and despised minority might have led to her public execution in the Roman arena. However, Marcia was neither particularly honored by the Christians nor condemned by the Roman authorities for her actions. This devaluation of Marcia in both pagan and Christian sources reveals its own story about the nature of early church politics, the complex intrigues of an Emperor’s court at the end of the high empire, and the ability of a lowly concubine to exert political influence and change the course of Western history.